INTERAKSI KEPRIBADIAN PENGARUHNYA TERHADAP DUKUNGAN POLITIK ORGANISASI SERTA DAMPAKNYA PADA PENINGKATAN KINERJA KONTEKSTUAL DOSEN (Studi pada Perguruan Tinggi Di Cirebon) - - Thamrin; - Badawi (Universitas Muhammadiyah Semarang, 2011)
The purpuse of this research in to examine the personality intraction make conduct concsientiousness,extraversion, agreeableeness, emosional stability and organization politic on contexctual performance. ThisResearch is to examine how to contribute variable to conduct personality have dimension concsientiousness,extraversion, agreeableeness, emosional stabilityObject this research University in Cirebon with responden is lecture take 120 respodent of University in theCirebon. Test analysis tool used is Structural Equation Modelling (SEM).The result of this research shows that personality formed concsientiousness extraversion,agreeableeness emosional stability, Personality significant and positive effect on organization politic.Organization politic not significant on contexctual performance. So first hypotesis is recieved and secondhypotesis not recieved